2015
DOI: 10.1111/apm.12419
|View full text |Cite
|
Sign up to set email alerts
|

Elevated levels of peripheral blood CD14brightCD16+ and CD14dimCD16+ monocytes may contribute to the development of retinopathy in patients with juvenile onset type 1 diabetes

Abstract: The study aimed to analyze the CD14(bright) CD16(+) and CD14(dim) CD16(+) monocyte subsets in juvenile-onset complication-free diabetes mellitus type 1 in the context of their association with microvascular complications. 61 children with type 1 diabetes and 30 healthy individuals were enrolled in a study. CD14(bright) CD16(+) and CD14(dim) CD16(+) monocytes were quantified in peripheral blood by means of flow cytometry. At the time of sampling blood glucose concentration was taken along with biochemical measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 24 publications
(37 reference statements)
2
10
0
Order By: Relevance
“…This causes change in a profile of released cytokines upon receptor activation [ 43 ]. Based on our results and literature [ 5 , 44 , 45 ] it is highly probable that CD16 + monocytes play an important role in promoting inflammatory response in DM1.…”
Section: Discussionsupporting
confidence: 65%
“…This causes change in a profile of released cytokines upon receptor activation [ 43 ]. Based on our results and literature [ 5 , 44 , 45 ] it is highly probable that CD16 + monocytes play an important role in promoting inflammatory response in DM1.…”
Section: Discussionsupporting
confidence: 65%
“…Diabetic macrophages are hyperresponsive to inflammatory stimuli in vitro, are less able to switch to alternatively activated phenotypes, and exhibit a prolonged inflammatory phenotype in diabetic wounds (4,11,29). There is also evidence for diabetes altering the number or phenotype of nonlassical monocytes in humans (30)(31)(32). Together with diabetes-induced changes in other myeloid cell lineages such as neutrophils (7), macrophages drive the elevated, nonresolving inflammatory state of chronic nonhealing diabetic wounds (33)(34)(35).…”
Section: Introductionmentioning
confidence: 99%
“…Enhanced monocyte activity, phenotype changes [9,10] and their ability to spontaneous production of pro-inflammatory cytokines [11] were recently reported in type 1 diabetes. In our previous works, we observed an increased number of non-classical and intermediate monocytes in peripheral blood of complication-free DM1 juvenile patients [12,13]. Others showed that DM1 subjects with late diabetic complications are characterised by a lower frequency of blood CD16 + cells in comparison with complication-free ones.…”
Section: Introductionmentioning
confidence: 63%